LC-MS/MS Profiling and Anti-inflammatory Activity of Red Onion (Allium cepa L. var. Bima Brebes) Extract-Based Liniment in Mus musculus - Saragih, Melisa; Harefa, Siwardin; Rahel, Kezia; Ruhi, Ratu Sukma; Rahmaningtyas, Ekarin Lativa; Eliasari, Laurencia Chrisiana; Riskianto, Riskianto (Tropical Biopharmaca Research Center, IPB University, 2026)
Allium cepa L. (Bima Brebes variety) is a prolific source of quercetin-type flavonols and organosulfur compounds, recognized for their potent anti-inflammatory and antioxidant activities. Topical herbal liniments offer a practical approach to manage localized inflammation while minimizing systemic exposure. This study aimed to evaluate the anti-inflammatory activity of a topical liniment formulated with a 70% ethanolic extract of A. cepa. LC–MS/MS (UHPLC Vanquish Tandem Q) had identified ten secondary metabolites putatively linked to anti-inflammatory effects. Anti-inflammatory efficacy was evaluated in vivo using a carrageenan-induced paw oedema model in male mice. Oedema inhibition was recorded at 18% in the negative control, 47% in the positive control, and 38%, 42%, and 44% for the 2 g, 3 g, and 5 g formulations, respectively. One-way ANOVA revealed significant differences among groups (p = 0.001). These findings suggested that A. cepa-based liniment formulations may serve as promising candidates as natural topical anti-inflammatory agents.